INTERNALISASI NILAI PENDIDIKAN KARAKTER MELAUI SATUA I KARUNA - I Nengah Arimbawa; I Nengah Adi Widana (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2021)
Education is now a basic need, which is expected to increase a person's life. However, starting in 2020 the world of education experienced a very significant turmoil, this was due to the Covid-19 pandemic. Where initially education was carried out face-to-face/directly, education was carried out in an "Online" network. This has become a separate problem in the world of education, especially when providing character education. The transfer of knowledge is indeed easy to carry out during online learning, but for character education itself, it has its own obstacles. Many efforts have been carried out by educators, one of which is by providing character education through stories or in Bali known as satua, one of which is satua entitled I Karuna which requires the value of character education. The method used in this paper is the hermeneutic method. Where hermeneutics is the study of understanding, especially about understanding in the form of text. The character education values contained in Satua I Karuna are 1) Religious Values, 2) Nationalist Values, 3) Integrity Values, 4) Independent Values, and 5) Mutual Cooperation Values.Keywords: internalization, character education, Satua I Karuna